ANALISIS KADAR MERKURI PADA BIOTA AIR DENGAN NANOPARTIKEL PERAK SECARA CITRA DIGITAL DI LOKASI PENAMBANGAN EMAS KABUPATEN LEBONG - Hendry Nordan; Mochamad Lutfi Firdaus; Rina Elvia (University of Bengkulu, 2020)
This study aimed at determining of how the sensitivity of silver nanoparticles (NPP) in detecting metal mercury in aquatic biota samples through digital imagery. The Sampling of aquatic biota was carried out in the gold mining location of Lebong Tambang village in Lebong district (102 ° 12'00